Persepsi Masyarakat terhadap Implementasi Electronic Traffic Law Enforcement (ETLE) di Pekanbaru - Rahma Rifki Ananda; Dipo Oktavian; Putri Sartika; Mohd. Robih Apriyanto (Router : Jurnal Teknik Informatika dan Terapan, 2025)
The increasingly complex traffic problems in Pekanbaru, marked by an increase in the number of vehicles, have prompted the government to implement Electronic Traffic Law Enforcement (ETLE) as an effort to improve public order and provide effective, efficient, transparent, and accountable public services. ETLE, which falls under the category of Smart Environment, uses camera and sensor technology to automatically detect various traffic violations. The implementation of ETLE in Pekanbaru began in March 2021 at four strategic locations. This study aims to examine the perceptions of Pekanbaru residents regarding the implementation of ETLE, including positive and negative aspects, as well as concerns related to system accuracy and flexibility in the field. Using a quantitative approach with a survey method, data was collected through questionnaires from 100 road users in Pekanbaru. The results of the study indicate that the public generally has a positive view of ETLE in creating traffic order and fairness, but there are also significant concerns regarding insufficient socialization, potential system errors, and procedural complexity. Implications: This study is expected to provide constructive input for authorities to improve the ETLE system and socialization strategies in the future